FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DAN PROSPEK USAHATANI KOPI RAKYAT DI DESA SUMBERBULUS KECAMATAN LEDOKOMBO KABUPATEN JEMBER - Ermadita Wahyu; Anik Suwandari (University of Jember, 2012)
The aim of the research are: (1) To know factors influence the income of farmers’, (2) To know average income of coffee farm management, (3) To know trend production and the field size of coffee. Research site was choosen by purposive. The sampling technique used simple random sampling. The data analysis used multiple linier regression, income, and trend analysis.The result of this research shows that: (1) Selling price, production, labour cost, fertilizer cost and farmers’ experience are significantly influence the income, otherwise field size and family member are unsignificantly influence the income (2) The income of coffee farm management is profitable and (3) Trend production and field size of coffee farm management in Sumberbulus Village will be increase for the next years. Keyword : coffee, income of coffee, trend production and the field size of coffee.